2022
DOI: 10.1186/s12885-022-09189-w
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to reducing chemotherapy for early-stage breast cancer: a qualitative analysis of interviews with patients and patient advocates

Abstract: Background As the combination of systemic and targeted chemotherapies is associated with severe adverse side effects and long-term health complications, there is interest in reducing treatment intensity for patients with early-stage breast cancer (EBC). Clinical trials are needed to determine the feasibility of reducing treatment intensity while maintaining 3-year recurrence-free survival of greater than 92%. To recruit participants for these trials, it is important to understand patient perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…1 By contrast, one of the strongest facilitators for optimization trial participation was recommendation by the physician to participate in the trial. 2 This finding underscored the importance of the physician's role in trial recruitment, which has been previously reported as a key driver in more traditional clinical trials. 3 Optimization trials may be uniquely accessible to community oncology practices because of the use of standard-of-care medications, which are available on-site and do not require learning new side effect profiles.…”
Section: Original Contributionsmentioning
confidence: 61%
See 1 more Smart Citation
“…1 By contrast, one of the strongest facilitators for optimization trial participation was recommendation by the physician to participate in the trial. 2 This finding underscored the importance of the physician's role in trial recruitment, which has been previously reported as a key driver in more traditional clinical trials. 3 Optimization trials may be uniquely accessible to community oncology practices because of the use of standard-of-care medications, which are available on-site and do not require learning new side effect profiles.…”
Section: Original Contributionsmentioning
confidence: 61%
“…1 By contrast, one of the strongest facilitators for optimization trial participation was recommendation by the physician to participate in the trial. 2 This finding underscored the importance of the physician's role in trial recruitment, which has been previously reported as a key driver in more traditional clinical trials. 3…”
Section: Introductionmentioning
confidence: 61%
“…There was strong evidence that patients from more deprived areas were less likely to receive chemotherapy or combination adjuvant chemotherapy. Trust in clinicians, financial and employment factors, social support, adequate communication and provision of information are critical in influencing the use of chemotherapy 58–61. These, among other uncaptured factors such as comorbidity or frailty, could be responsible for the observed inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…Trust in clinicians, financial and employment factors, social support, adequate communication and provision of information are critical in influencing the use of chemotherapy. [58][59][60][61] These, among other uncaptured factors such as comorbidity or frailty, could be responsible for the observed inequalities.…”
Section: Diagnostic and Treatment Delaysmentioning
confidence: 99%
“…This qualitative sub‐study is part of a larger project evaluating oncologist perspectives on optimization‐focused clinical trials for breast cancer patients. 2 , 5 Purposive sampling techniques were utilized to identify a balanced convenience sample of oncologists according to setting, gender, ethnicity, age, years of experience, and geographic location. In‐depth sample methodology and oncologist characteristics are described elsewhere.…”
Section: Methodsmentioning
confidence: 99%